Treatment Outcomes for Osteoradionecrosis of the Central Skull Base: A Systematic Review - Shaikh, Noah; Makary, Chadi A.; Ryan, Lindsey; Reyes, Camilo (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective Osteoradionecrosis (ORN) of the skull base can have catastrophic consequences if not detected early and managed appropriately. This is a systematic review of the different treatment modalities for skull base ORN and their outcomes.Study Design This study is a systematic review.Materials and Methods Two researchers extracted information including patient population, surgical technique, outcomes of interest, and study design. A computerized search of Medline, Embase, and the Cochrane library (January 1990–June 2020) looked for several papers on the subject of skull base ORN.Results A total of 29 studies had met inclusion criteria, including data from 333 patients. Nasopharyngeal carcinoma was the most common primary tumor (85%). Average age at diagnosis of ORN was 55.9 years (range = 15–80 years) and 72.3% of patients were males. The average time to diagnosis of ORN after radiation therapy was 77 months with an average radiation dose of 76.2 Gy (range = 46–202 Gy). Nighty-eight patients (29.4%) also had chemotherapy as part of their treatment regimen. Although all parts of the central skull base were reported to be involved, the clivus and sphenoid bone were the most commonly reported subsites. Trial of medical treatment had a success rate of 41.1%. About 66% of patients needed surgical treatment, either primarily or after failing medical treatment. Success rate was 77.3%. Overall, the surgical treatment was superior to medical treatment (p < 0.0001).Conclusion ORN is a rare complication of the treatment of skull base tumors. Most cases require surgical treatment, including endoscopic debridement or free flap reconstruction, which has a high success rate.Level of Evidence Level 3 evidence as a systematic review of case studies, case reports, retrospective, and prospective trials with no blinding or controls.
Keywords: osteoradionecrosis; skull base; reconstruction; side effects; rhinology; evidence-based medicine; radiation therapy; systematic review; outcome